MOTIVASI PEMERINTAH INDONESIA MENERAPKAN BEBAS VISA TERHADAP EL SALVADOR - Giovani "; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research will explain about Indonesian government policy in making a visa-free agreement towards El Salvador. Indonesia and El Salvador began to establish diplomatic relations in 2011. Relations between Indonesia and El Salvador more closely in caused both countries are equally members of the Forum of East Asia - Latin America coorporatin ( FEALAC ) . In 2013 Indonesia and El Salvador agreed to the opening of the bilateral cooperation relations between the two countries. Furthermore, both countries have visa-free agreement in 2015.Sources were obtained through literature review from journals, books, mini thesis, reports, and internet to explain why Indonesian government imposed a visa-free policy. the author uses the realist perspective to explain the Indonesian government policy and using the theory of foreign policy.This research indicates the reason of Indonesian government imposed a visa-free policy toward El Salvador is to open up a new market for Indonesian exports . Because Indonesia's exports slow compared with the previous year because Indonesian exports in the five countries which are the main export destinations of Indonesia and the European are in crisis.Keywords: visa-free agreement, Indonesia’s foreign policy, Bilateral cooperation